The presidency in a separated system - Jones, Charles O.; ebrary, Inc. (Washington, D.C. : Brookings Institution Press, 2005)
"Examines the organizational, political, and procedural challenges faced by postwar U.S. presidents, from Truman through George W. Bush, working in a separated system of government"--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Presidents -- United States -- History; Separation of powers -- United States; United States -- Politics and government; Electronic books